Seroprevalence and predominant serogroups of Leptospira sp. in serological tests of ruminants in northeastern Brazil - Carla Lauise Rodrigues Menezes Pimenta; Camila de Sousa Bezerra; Davidianne de Andrade Morais; Maria Luana Cristiny Rodrigues Silva; Denise Batista Nogueira; Diego Figueiredo da Costa; Carolina de Sousa Américo Batista Santos; Severino Silvano dos Santos Higino; Clebert José Alves; Sérgio Santos de Azevedo (Semina: Ciências Agrárias, 2019)
The objective of this study was to determine the seroprevalence of leptospirosis and the predominant serogroups in serological tests of ruminants performed at the Transmissible Diseases Laboratory of the Federal University of Campina Grande, Patos, Paraíba, northeastern Brazil, between 2010 and 2017. This research included the records of serological tests for leptospirosis from 5594 animals, including 1527 cattle, 1761 goats, 2170 sheep, and 136 buffaloes from four Brazilian states (Paraíba, Pernambuco, Maranhão, and Rio Grande do Norte). Of the 5594 serum samples, 662 were serologically positive, corresponding to a frequency of 11.8%. Serjoe (30.6%), Autumnalis (13.6%), and Icterohaemorrhagiae (11.3%) were the most frequent subgroups among all species. The individual frequencies in cattle, goats, sheep, and buffaloes were 20% (306/1527), 8.3% (147/1761), 7.9% (171/2170), and 27.9% (38/136), respectively, with titers ranging from 1:100 to 1:3200. The most frequent serogroups according to animal species were as follows: Serjoe predominated in cattle (62%), followed by Icterohaemorrhagiae (12.5%) and Tarassovi (6.6%); Autumnalis was the most frequent in goats and sheep (29.4% and 26.9%, respectively), followed by Seramanga (12.5%) in goats and Icterohaemmorrhagiae (13.5%) in sheep; and Australis predominated in buffaloes (39.5%), followed by Pomona (31.6%) and Canicola (21.1%). Leptospira sp. infection, determined by serology, is widespread in ruminants (cattle, goats, sheep, and buffaloes) in northeastern Brazil, suggesting the existence of alternative transmission routes that are less dependent on environmental factors. Identification of the most frequent serogroups highlights the need to improve sanitary conditions, and implement efficient and targeted control measures directed at the primary infection sources.